An improved secure authentication in lightweight IoT - Mohd Ariffin, Noor Afiza; Paliah, Vanitha (Semarak Ilmu Publishing, 2023)
Internet of Things (IoT) has been widely accepted by users and with rapid development of cloud computing, users are able to access the IoT services in various environment, including smart home, healthcare and smart factory. However, users are insecure as their data is being transmitted via open communication channel. The previous research protocol does not resist insider attack which leads to insecure scheme. In this proposal, we propose an enhanced security measurement to resist insider attack. The proposed scheme expected to achieve security requirements and resist insider attack. The proposed scheme will be validated using the automated validation of internet security protocols and applications (AVISPA) simulation tool and we will compare the performance and security features of the existing scheme and the proposed scheme.